Efficacy and mechanisms of behavioral therapy components for insomnia coexisting with chronic obstructive pulmonary disease: study protocol for a randomized controlled trial. Issue 1 (December 2016) - Kapella, Mary; Herdegen, James; Laghi, Franco; Steffen, Alana; Carley, David
Abstract Background Difficulty falling asleep, staying asleep or poor-quality sleep (insomnia) is common in people with chronic obstructive pulmonary disease (COPD). Insomnia is related to greater mortality and morbidity, with four times the risk of mortality for sleep times below 300 min. However, insomnia medications are used with caution in COPD due to their potential adverse effects. While cognitive behavioral therapy for insomnia (CBT-I) is effective for people with primary insomnia and people with other chronic illnesses, the efficacy and mechanisms of action of such a therapy are yet unclear in people with both insomnia and COPD. The purpose of this study is to rigorously test the efficacy of two components of insomnia therapy – CBT-I and COPD education (COPD-ED) – in people with coexisting insomnia and COPD, and to identify mechanisms responsible for therapy outcomes. The rationale for the proposed study is that once the efficacy and mechanisms of CBT-I and COPD-ED are known, new and innovative approaches for insomnia coexisting with COPD can be developed to non-pharmacologically minimize insomnia and fatigue, thereby leading to longer, higher-quality and more productive lives for people with COPD, and reduced societal cost due to the effects of insomnia. Methods We are conducting a randomized, controlled, parallel-group (N = 35 each group) comparison of CBT-I, COPD-ED and non-COPD, non-sleep health education Attention Control (AC) using a highly efficient four-group design. Arm 1 comprises 6 weekly sessions of CBT-I + AC; Arm 2 = 6 weekly sessions of COPD-ED + AC; Arm 3 = 6 weekly sessions of CBT-I + COPD-ED; and Arm 4 = 6 weekly sessions of AC. This design will allow completion of the following specific aims: (1) to determine the efficacy of individual treatment components, CBT-I and COPD-ED, on insomnia and fatigue, (2) to define the mechanistic contributors to the outcomes after CBT-I and COPD-ED. Discussion The research is innovative because it represents a new and substantive departure from the usual insomnia therapy, namely by testing traditional CBT-I with education to enhance outcomes. The work proposed in aims 1 and 2 will provide systematic evidence of the efficacy and mechanisms of components of a novel approach to insomnia comorbid with COPD. Such results are highly likely to provide new approaches for preventive and therapeutic interventions for insomnia and fatigue in COPD. Trial registration ClinicalTrials.gov Identifier:NCT01973647 . Registered on 22 October 2013.